$V$-Limit Analysis of Vector-Valued Mappings - Kogut, P. I.; Rudyanova, Т. M. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For an arbitrary net of mappings defined on subsets of the Hausdorff space (X, τ) and acting into a vector topological space (Y, τ) semiordered by a solid cone Λ, we introduce the notion of V-limit. We investigate topological and sequential properties of V-limit mappings and establish sufficient conditions for their existence. The results presented can be used as a basis for the procedure of averaging of problems of vector optimization.